2019
DOI: 10.1002/ejic.201801259
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Dioxide and the Antioxidant Properties of Catechols

Abstract: Complexes of tetra-and hexa-coordinated germanium Adr Cat 2 Ge (1, Adr Cat = adrenaline catecholate), Ald Cat 2 Ge (2, Ald Cat = 4-formylcatecholate), Ald Cat 3 Ge(Et 3 NH) 2 (3) were synthesized by the reaction of germanium dioxide with adrenaline and 3,4-dihydroxybenzaldehyde in aqueous solution. The structures of the complexes were confirmed by 1 H and 13 C NMR and IR spectroscopy, HRMS, and elemental analysis. Cyclic voltammetry in phosphate buffer solutions (pH = 6.86) has shown the oxidation potentials E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Melatonin (N-acetyl-5-methoxytryptamine) as an effective antioxidant [ 61 ] could be ultimately oxidized to 5-methoxyindole-3-acetic acid [ 62 ]. Hence, the level of 5-methoxyindole-3-acetic acid in Group H with higher RDP density was significantly higher than that in Group C. In this study, catechol as an antioxidant [ 63 , 64 ] was positively related to the relative abundances of Ruminococcus _2 and Prevotella_ 1, which might imply that high energy and protein levels in Group H could enhance the catechol concentration by these two genera. Xue et al [ 65 ] reported that the content of spermidine increased in the group of high concentrate diets (rich in starch), which is in line with the results of our study.…”
Section: Discussionmentioning
confidence: 58%
“…Melatonin (N-acetyl-5-methoxytryptamine) as an effective antioxidant [ 61 ] could be ultimately oxidized to 5-methoxyindole-3-acetic acid [ 62 ]. Hence, the level of 5-methoxyindole-3-acetic acid in Group H with higher RDP density was significantly higher than that in Group C. In this study, catechol as an antioxidant [ 63 , 64 ] was positively related to the relative abundances of Ruminococcus _2 and Prevotella_ 1, which might imply that high energy and protein levels in Group H could enhance the catechol concentration by these two genera. Xue et al [ 65 ] reported that the content of spermidine increased in the group of high concentrate diets (rich in starch), which is in line with the results of our study.…”
Section: Discussionmentioning
confidence: 58%
“…Melatonin (Nacetyl-5-methoxytryptamine) as an effective antioxidant [70] could be ultimately oxidized to 5methoxyindole-3-acetic acid [71]. Hence, the level of 5-methoxyindole-3-acetic acid in Group H with higher protein diets was signi cantly higher than that in Group C. In this study, catechol as an antioxidant [72,73] was positively related to the relative abundances of Ruminococcus_2 and Prevotella_1, which might imply that high energy and protein levels in Group H could enhance the catechol concentration by these two genera. Xue et al [74] reported that the content of spermidine increased in the group of high concentrate diets compared with moderate concentration of diets, which is in line with our study.…”
Section: Comparison Of the Composition And Differences Of Ruminal Metmentioning
confidence: 63%
“…1a). [15] At the same time, occupying one valence of Ge with an organic substituent, the carboxyethyl group, prevents the resulting product from packing into dense 3D forms and renders its structure more susceptible to penetration of water molecules and consequently to hydrolysis (Fig. 1b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%